Design of wearable textile patch antenna using C-Shape etching slot for Wi-Max and 5g lower band applications - Mahfuz, M. M. Hasan; Islam, Md. Rafiqul; Sakib, Nazmus; Habaebi, Mohamed Hadi; Raad, Raad; Sakib, Md Abu Tayab (IEEE, 2021)
Because of the technology that is demanded today’s the microstrip patch antennas have more strength and flexibility. Different studies of antennas have shown that it can operate on different frequencies, at lowing for a large number of applications such as medical, military and so many applications. So, a textile antenna is presented for the Wi-MAX (3.09–3.94) GHz and 5G lower band (4.23–5.65) GHz applications in this manuscript. The proposed wearable textile antenna designed on textile substrate of jeans in order to minimize surface wave losses. There is a patch with C-shape etching slot (CSES) and a defected ground in the planned antenna configuration. A microstrip line feed technique is used in the design to develop the wearable textile antenna. It was determined that its utmost SAR is 0.353 W/kg which is less than 2 W/kg of 10 gm human tissue, for the observation of the radiation effect. This parametric analysis is carried out to check that the antenna is working properly.